Quadratic Programming Thrust Allocation and Management for Dynamic Positioning Ships - Yushi Wei; Mingyu Fu; Jipeng Ning; Xingyan Sun (Institute of Advanced Engineering and Science, 2013)
To solve the complex thrust allocation problems of dynamic positioning ship with azimuth thrusters, the quadratic programming thrust allocation and management system was built. The power optimal thrust allocation was formulated as a quadratic programming problem by the linear treatments of inequality constraints and the optimal solution could be found in a finite amount of time. And some influence factors of thruster allocation were separated from algorithms and treated as a superstratum management module. In this system, online adjustment of input constraints and singularity avoidance could be realized, and the reliability and adaptability of thrust allocation were improved consequently. Finally, the validity and excellent performance of this method was proved by the simulation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2318